INTERPRETASI PENDIDIKAN AGAMA HINDU DALAM TRADISI MAPPADENDANG DI DESA LAINUNGAN KABUPATEN SIDRAP SULAWESI SELATAN - Harmi T; I Gusti Ngurah Sudiana; I Nyoman Alit Putrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
One of the areas inhabited by the Bugis tribe in South Sulawesi is Sidenreng Rappang Regency. The Bugis tribe has various traditions or customs spread across several areas in South Sulawesi Province, such as Sidrap Regency, which to this day still maintains its traditional harvest festival traditions which are now starting to be forgotten along with increasingly modern developments. The harvest party tradition in question is Mappadendang, this tradition reminds of the cosmology of everyday life of rural farmers. The above problems are studied using several theories. The theories used are Extensional Theory, Hermeunetic Theory, and Value Theory. Meanwhile, the methods used to collect data are observation, interviews, literature study, documentation study and explained using descriptive methods, so that comprehensive conclusions are obtained. This type of research uses descriptive qualitative research methods. The results of the research show that the Mappadendang tradition has been carried out for generations, the Mappadendang tradition is carried out by the Bugis community as a form of gratitude for the success of the harvest and is a place to socialize between fellow Bugis communities so that they can strengthen social relations between communities both from the local area and from outside the Sidrap area. In the process of implementing the Mappadendang traditional party, it has an appropriate implementation time and must follow ancestral traditions and there are no farming activities during the harvest party. Apart from the time that has been determined, the Mappadendang traditional tradition also includes stages and preparations which include determining the day and length of time for its implementation, as well as the tools that need to be prepared which will be used by the players in implementing Mappadendang.